Anti‐tumour activity of oncolytic reovirus against canine histiocytic sarcoma cells. (13th March 2019) - Igase, Masaya; Shousu, Kazuha; Fujiki, Noriyuki; Sakurai, Masashi; Bonkobara, Makoto; Hwang, Chung C.; Coffey, Matt; Noguchi, Shunsuke; Nemoto, Yuki; Mizuno, Takuya
Abstract : Canine histiocytic sarcoma is an aggressive, fatal neoplastic disease with a poor prognosis. Lomustine is generally accepted as the first‐line systemic therapy, although this compound does not provide complete regression. Therefore, research into a novel approach against canine histiocytic sarcoma is needed. However, anti‐tumour effects of oncolytic therapy using reovirus against histiocytic sarcoma are unknown. Here, we showed that reovirus has oncolytic activity in canine histiocytic sarcoma cell lines in vitro and in vivo. We found that reovirus can replicate and induce caspase‐dependent apoptosis in canine histiocytic sarcoma cell lines. A single intra‐tumoural injection of reovirus completely suppressed the growth of subcutaneously grafted tumours in NOD/SCID mice. Additionally, we demonstrated that susceptibility to reovirus‐induced cell death was attributable to the extent of expression of type I interferons induced by reovirus infection in vitro. In conclusion, oncolytic reovirus appears to be an effective treatment option for histiocytic sarcoma, and therefore warrants further investigation in early clinical trials.